Knowledge of General Dentists and Senior Dental Students about Indications of Antibiotic Prophylaxis in Yazd, Iran - Fahimeh Rashidi Maybodi; Elaheh Hafizi Barjin; Mohammad-Hassan Akhavan Karbassi (Mashhad University of Medical Sciences, 2018)
Introduction: In patients susceptible to infection, after dental procedures which lead to soft tissue manipulation or bleeding, the occurrence of bacteremia is probable. Hence, antibiotic prophylaxis is very important in this group of patients. The purpose of this study was to assess the level of awareness of senior dental students and general dental practitioners in the city of Yazd about the indications of antibiotics prophylaxis and the proper way of prescribing the prophylactic regimens. Materials and methods: This study is a cross-sectional descriptive-analytical study. To collecting data, prepared questionnaires distributed among 60 general dentists and 60 senior students. Results: The mean of knowledge scores of senior dental students and general dentists were 55.43  and 55.06  respectively. Both groups showed acceptable levels of knowledge. Conclusion: The levels of knowledge of senior dental students and general dental practitioners were desirable and this may be due to the participation of practitioners in relevant re-training programs or allocation of related academic resources in this area during their education.